2006
DOI: 10.1186/1477-7827-4-26
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ion currents mediating oocyte maturation events

Abstract: During maturation, the last phase of oogenesis, the oocyte undergoes several changes which prepare it to be ovulated and fertilized. Immature oocytes are arrested in the first meiotic process prophase, that is morphologically identified by a germinal vesicle. The removal of the first meiotic block marks the initiation of maturation. Although a large number of molecules are involved in complex sequences of events, there is evidence that a calcium increase plays a pivotal role in meiosis re-initiation. It is wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 123 publications
5
61
0
5
Order By: Relevance
“…Moreover, ion channel currents (e.g. calcium currents) are involved in oocyte maturation and fertilization in vertebrate and invertebrate animals (Tosti, 2006; Tosti and Boni, 2004). Therefore, given that AgKir1 expression is enriched in the ovaries and that AgKir1 gene silencing reduces fecundity, it is possible that AgKir1 may participate in the regulation of mosquito oocyte maturation by modulating membrane excitability in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ion channel currents (e.g. calcium currents) are involved in oocyte maturation and fertilization in vertebrate and invertebrate animals (Tosti, 2006; Tosti and Boni, 2004). Therefore, given that AgKir1 expression is enriched in the ovaries and that AgKir1 gene silencing reduces fecundity, it is possible that AgKir1 may participate in the regulation of mosquito oocyte maturation by modulating membrane excitability in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of Ca 2+ entry through plasma membrane channels during oocyte maturation has been described only in few mammalian species [38][40]and mollusks [9], [11], [41][46]. In the majority of cases, the currents responsible for Ca 2+ influx have been shown to be L-type Ca 2+ currents [10], [17][19].…”
Section: Discussionmentioning
confidence: 99%
“…The role of ion currents in the gametes physiology has been well described in many animal species [7], [11], [13]–[16]. A pivotal role in gamete physiology is played by different types of voltage dependent Ca 2+ currents; in particular, it has been shown that the high threshold L-type Ca 2+ currents are either expressed in the immature oocytes and modulate oocyte growth, cytoplasmic maturation and early embryo development in a variety of organisms [9], [10], [17][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the precise molecular mechanism of this Ca 2þ influx at fertilization and the nature of the Ca 2þ channels or transporters involved in this event. In this regard, a recent review highlights the involvement of voltage-operated calcium channels (VOCs) during oocyte maturation from germinal vesicle to metaphase II (MII) oocytes [13], although the relative contribution of a broad range of plasma membrane calcium channels during early signaling in mammalian fertilized oocytes remains unclear. In other somatic cell types, such as neurons, smooth muscle cells, and a variety of endocrine cells, it is well established that calcium waves triggered by diverse stimuli are dependent on the process of calcium entry through plasma membrane in order to replenish calcium levels in Ca 2þ stores to maintain the rapid rate of cytosolic Ca 2þ spiking.…”
Section: Introductionmentioning
confidence: 99%